Potensi Antibakteri Gel Angkak (Monascus purpureus JmbA Rice) terhadap Jumlah Leukosit pada Penyembuhan Luka Akut Diabetes - Annisa Nuzilati Rachma (Fakultas Kedokteran, 2024)
Diabetic wounds are one of the most common complications of DM due to macrovascular disorders of peripheral vascular disease. Bacterial infection on the wound causes the healing process to be inhibited. Inappropriate use of antibiotics leads to bacterial resistance and excessive cytotoxicity. Monascus purpureus JmbA rice (MJR) is a red yeast rice that has antibacterial activity due to the presence of monascidin A compounds that can inhibit bacterial growth. The purpose of this study was to determine the antibacterial effectiveness of angkak gel (Monascus purpureus JmbA Rice) on leukocyte counts in acute diabetic wound healing. This study is a true experimental design with the post-test only randomized control group method. Data analysis of the average leukocyte count of 40% red yeast rice gel treatment group on termination day 4th showed the lowest average with significant results p=0.050 compared to the negative control group of 0% red yeast rice gel. Data analysis on termination day 11th of the 80% red yeast rice gel group showed the lowest average and significant p=0.050 compared to the gel group of 0% red yeast rice gel. The results of data analysis on the 18th termination day showed that the 40% red yeast rice gel group and Bioplacenton had the lowest average leukocytes and were significantly different from the gel group of 0% red yeast rice gel. This study concluded that angkak gel with a certain concentration has antibacterial potential by effecting the leukocyte infiltration in diabetic acute wound healing.
Entry oleh Arif 2026 Maret 05
Keywords: Diabetes mellitus; Diabetic wound; Red yeast rice; Antibacterial